2015
DOI: 10.4000/histoiremesure.5189
|View full text |Cite
|
Sign up to set email alerts
|

Institutions historiques et développement économique en Afrique

Abstract: Institutions historiques et développement économique en Afrique. Une revue sélective et critique de travaux récents Résumé. Cet article effectue une revue sélective de travaux récents d'économistes étudiant l'impact des institutions historiques sur le développement économique en Afrique. Nous discutons d'abord quelques questions conceptuelles impliquées par la mesure des institutions, puis présentons les données rassemblées par l'anthropologue G. P. Murdock et leurs principales critiques. Plusieurs travaux mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In rows ( 1) and (1b) I excluded population density and included instead a non-linear function of (log) total population kinked at 50,000 people. This specification is due to Cogneau and Dupraz (2014), who showed that there is a non-linear relationship between population density and luminosity, flat at low levels of population and positive at higher levels. In rows ( 2) and (2b), I checked the sensitivity of results to the presence of sparsely populated areas, by excluding districts with less than 50,000 inhabitants.…”
Section: Colonial Price Gaps and Current Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In rows ( 1) and (1b) I excluded population density and included instead a non-linear function of (log) total population kinked at 50,000 people. This specification is due to Cogneau and Dupraz (2014), who showed that there is a non-linear relationship between population density and luminosity, flat at low levels of population and positive at higher levels. In rows ( 2) and (2b), I checked the sensitivity of results to the presence of sparsely populated areas, by excluding districts with less than 50,000 inhabitants.…”
Section: Colonial Price Gaps and Current Developmentmentioning
confidence: 99%
“…The idea is to measure the effect of price gaps on the majority of African population and not on the average inhabitant of sparsely populated regions (Cogneau and Dupraz, 2014). In rows ( 4) and (4b), I included districts above the 10 th percentile of luminosity.…”
Section: Colonial Price Gaps and Current Developmentmentioning
confidence: 99%